INFLUENCE OF BREED, AGE, SIZE AND PARITY OF THE DAM ON THE FREQUENCY DISTRIBUTION OF DYSTOCIAS IN CANINES - NARASIMHA , MURTHY; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2023)
The influence of breed, age, size and parity of the bitch on the incidence of dystocia was analyzed. Nearly30 per cent of dystocia cases presented (n=1236) were either in Labrador Retriever or German Shepards.However, 23.63 per cent of all dystocia encountered were in brachycephalic breeds like Pug, Bull dog andBoxers. The size of the breed was found to have a significant effect on the incidence of dystocia, the incidencebeing significantly higher in medium and large size breed. It was also observed that the incidence of thedystocia was highest in bitches aged 2-4 years and gradually declined with the advancing age. Bitches lessthan 4 years accounted for nearly 62 per cent of the dystocia cases suggesting the preference of owners tobreed animals at their younger age and withhold breeding in aged animals. In the present study 31.07 per centof cases referred were primiparous and the rest had delivered 1-8 times. The incidence of dystocia decreasedprogressively with increase in parity and the least incidence was recorded in animals with more than 5 previousdeliveries.
Keywords: Canine dystocia; Incidene; Breed; Age; Parity